Bilateral Relations of Indonesia and Pakistan During President Joko Widodo's Occupation In The Analytical Framework of KJ Holsti - Windy Khairunnisa, Brilliant (Ridwan Institute, 2021)
President Joko Widodo was viewed as more involved in the economy and infrastructure throughout his term. This is no exception when it comes to developing bilateral relations with Pakistan, which has a long history of excellent connections with Indonesia. This is bolstered by President Joko Widodo's objective of increasing commerce between Indonesia and Pakistan. The purpose of this paper is to examine the bilateral relationship between Indonesia and Pakistan during President Joko Widodo's tenure, particularly in the areas of economy and tourism, using KJ Holsti's foreign policy analysis, which considers the leader's political personality as well as the strategic environment in national circumstances. Qualitative research methods with secondary data are used in this study. The findings of this study, on the other hand, suggest that President Joko Widodo's history as an entrepreneur and the occurrence of financial deficits in the past are the driving forces behind the economic policies implemented. In terms of the strategic environment, bilateral cooperation is being stressed more heavily in order to mitigate the impact of the US-China trade war and to promote transactions and diplomacy between the two nations, similar to what transpired between Pakistan and Indonesia.